Ecosystem of VAT Administration in E-Commerce: Case of the Eastern Europe Countries - Abramova, A; Shaposhnykov, K; Zhavoronok, A; Liutikov, P; Skvirskyi, I; Lukashev, O (Estudios de economía aplicada, 2021)
Quarantine economic conditions put forward new demands to tax administration’s efficiency as a priority source of the EU financial resources. The relationship between fair, efficient, sustainable taxation and budget revenues’ adequacy to finance social and economic investment, innovation, and development needs is evident. Therefore, ensuring tax administration’s efficiency and effectiveness in any EU country is of theoretical and practical importance. The study aims to deepen the theoretical and applied provisions of the VAT administration in e-commerce operations in a global convergence of the national economic systems. The analysis of the state and forecast of the VAT mobilization in the EU countries’ e-commerce operations are presented. The research’s specific is to assess the VAT tax base’s future size in the context of changes in the EU tax legislation. According to the scientific literature analysis, in the framework of forecasting the studied tax, it is advisable to use econometric forecasting methods based on time series models. As the result of the study, the forecast volumes of the VAT base of Eastern Europe and the amount of approximate future tax revenues are presented. The obtained results confirm the relationship between the growth of e-commerce and VAT tax revenues under such transactions. It led to the presentation of the author’s vision of the VAT administration ecosystem for e-commerce transactions and the allocation of its functional entities. The directions on achieving the maximum volumes of the VAT mobilization following the EU tax legislation requirements in European integration and globalization were substantiated. The submitted conclusions are entitled to be used in tax administration processes in the matters of forecasting other tax payments.
Keywords: tax administration, VAT, fiscal stimulus, e-commerce.